MDP IS SIGNIFICANT TO THE INDUSTRY AND SUSTAINABLE DEVELOPMENT - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 31 May 2016 – The Master’s in Development Practice (MDP) academic programme offered at the 28 higher educational institutions around the world is of great significance and contributes to sustainable development globally.